PELATIHAN BERMAIN KATA UNTUK MENINGKATKAN KEMAMPUAN MEMBACA SISWA KELAS 1 SD DI KABUPATEN SEMARANG - Yuniawati, Rudy (Universitas Ahmad Dahlan, 2010)
The purpose of this research was to examine if there would be increasing in reading capability on the first grade students of elementary school, after getting the game word training. The training referred to the theory of reading capability by Scanovich. Some aspects were developed in this training; they were word recognition, vocabulary understanding, syntax under-standing, and contextual using. The subject of this research was 8 first grade students of elementary school who were not fluent in reading. They were divided into control group and experiment group. Data were collected by using reading capability test and observation. Both of group got reading capability test three times, namely, pre test, post test and once week after treatment. The result showed that there was significantly increasing of the students´ reading capability score on experiment group after getting the game word training. It can be concluded that the game word training is effective on increasing the students´ reading capability of the first grade of elementary school.